Evidence of HIV pre-exposure or post-exposure prophylaxis (PrEP/PEP) among blood donors: a pilot study, England June 2018 to July 2019. (29th March 2021) - Harvala, Heli; Reynolds, Claire; Ijaz, Samreen; Maddox, Vicki; Penchala, Sujan Dilly; Amara, Alieu; Else, Laura; Brailsford, Susan; Khoo, Saye
Abstract : Objective: Due to increased use of pre-exposure prohylaxis (PrEP) and its potential to affect HIV screening of blood donors, we undertook antiretroviral residual testing among HIV-negative male donors in England. Methods: Residual plasma samples were obtainnd from 46 male donors confirmed positive for syphilis and 96 donors who were repeat reactive for HIV antibodies in screening but confirmed as HIV-negative by reference testing. These were tested for concentrations of tenofovir and emtricitabine by high-performance liquid chromatograhpy coupled with mass spectrometry. Results: We found evidence of pre-exposure or post-exposure prophylaxis (PrEP/PEP) use in three male blood donors confirmed positive for syphilis (3 out of 46 screened, 6.5%). Two were estimated to have taken PrEP/PEP within a day of donating, and the third within 2 days. Two were new donors, whereas one had donated previously but acquired syphilis infection after his last donation. Conclusions: Our findings indicate that a small proportion of blood donors have not been disclosing PrEP/PEP use and therefore donating in non-compliance to donor eligibility criteria.